The development of intelligent solid waste trap machine using arduino uno - Zubaidah Abdul Rahman (Journal of Counseling and Educational Technology, 2022)
Poor drainage system in Malaysia is not a newly phenomenon among our society. The unethical activities of dumping rubbish into the drain, literally causing the flash flood due to clogged drains, in particular within the urban areas. The Intelligent Solid Waste Trap Machine Using Arduino is designed to collect rubbish in the domestic drain and capable in collecting rubbish up to capacity of 10kg. This automated machine is 50% mechanics and 50% electronics, functioning based on two microcontrollers. This waste trap machine is the most reliable and effective for promoting the sustainable drainage management in Malaysia at a lower cost. By adding IoT to this machine in future, some manual process can be carried out remotely. Thus, it helps local authorities to collect data on the trend of dumping into drains in certain areas.